Gp96 Expression in Gliomas and Its Association with Tumor Malignancy and T Cell Infiltrating Level. (26th June 2022) - Li, Chunzhao; Wang, Yi; Long, Lang; Zhang, Peng; Zhang, Yang; Ji, Nan
Abstract : Heat shock protein glycoprotein 96 kDa (gp96) implicates in glioma invasiveness and engages antitumor immune response, representing a potential target for glioma treatment. However, its expression in different types of gliomas, its association with glioma-infiltrating T cells (GITs), and their clinical significance remain unknown. Herein, we utilized multiplex immunofluorescence staining (MIS) to detect gp96 expression and GIT levels on a tissue microarray (TMA), that comprises 234 glioma cases. We then validated the TMA results and explored possible mechanisms by investigating the RNA-seq data from The Cancer Genome Atlas (TCGA) and the Chinese Glioma Genome Atlas (CGGA). We observed that gp96 was ubiquitously expressed in all types of gliomas whereas overexpressed in grade IV gliomas. Also, high gp96 expression predicted unfavorable outcomes independent of the malignancy grade. Meanwhile, gp96 expression positively correlated CD8 +, CD4 +, and PD-1 + cell densities, and especially associated with increased infiltration of CD4 + PD-1 + GITs. Clinically, the gp96-immune cell score (GI score), by summing the values measuring gp96 expression and immune cell densities, is capable of stratifying patients into four outcome-distinct groups (hazard ratio, 1.945; 95% CI, 1.521–2.486; P < 0.0001 ). Mechanistically, the interferon- γ / α response pathways were revealed to engage in the association between gp96 and GITs. Taken together, gp96 was ubiquitously expressed in gliomas, overexpressed in grade IV gliomas, and increased with GIT infiltrative levels. The GI score, that integrates levels of gp96 expression and GIT infiltration, is a potential prognostic classification system for gliomas.